Natural Product Dietary Supplement Use by Individuals With Rheumatoid Arthritis: A Scoping Review. Issue 6 (3rd May 2019) - DeSalvo, Janel C.; Skiba, Meghan B.; Howe, Carol L.; Haiber, Karen E.; Funk, Janet L.
Abstract : Objective: Natural product dietary supplements (NDS), defined as non‐mineral, non‐vitamin, ingested, natural product–derived, substances, are the most frequently used complementary and alternative medicine modality in the US, with musculoskeletal disease being the most frequent reason for their use. Because NDS usage is frequently unreported, and patients with RA may be at higher risk for NDS‐related side effects due the underlying nature of the disease and frequent use of complex pharmaceutical regimens, a scoping review of the literature was undertaken to examine population‐based patterns of NDS use for RA self‐management. Methods: Using guidelines for scoping reviews, Allied and Complementary Medicine, the Cumulative Index to Nursing and Allied Health Literature, the Cochrane Library, Embase, Ovid/Medline, and Web of Science databases were searched to identify references presenting primary data related to the prevalence or patterns of use of NDS in RA populations. Results: Twenty‐three studies, which were published between 1980 and 2015 and conducted in 11 countries, met the inclusion criteria. The overall prevalence of NDS use in patients with RA was 47% worldwide and did not differ by geographic region. On average, 47% of patients found NDS to be effective and 13% reported adverse side effects, with only 30% informing their physicians about the use of NDS, which in a majority of cases were used concomitantly with RA pharmaceuticals. Marine oils, glucosamine, vinegar, and chondroitin were among the most commonly reported NDS worldwide. Conclusion: Given the apparent communication gap between patients and providers regarding NDS use and higher potential risks associated with this usage in RA, ongoing surveillance of population‐based practices may help facilitate RA management and direct future NDS research.